Soviet Trade in the 1960s — 1980s: Basic Principles and Their Distortion - A. S. Stoletova (Научный диалог)
The article reveals the problem of distortion of the socialist principles of Soviet trade in the economic practice of the state of the 1960s — 1980s, which is insufficiently illuminated in historical science, using the example of letters from Soviet citizens collected in the fund of the Russian State Archive of Contemporary History. Based on a review of a significant amount of archival sources, various kinds of deformations occurring in trade activities and their fixation in the public mind are demonstrated. It is emphasized that people’s ideas were the most important dimensions of social life, the economic dynamics of Soviet society and the social psychology of citizens. Particular attention is paid to the analysis of legislation as the main mechanism for regulating the development of the trade and economic area. It is argued that the lack of formation of the regulatory framework gave rise to such reality phenomena as deficit, overcharging, short weight and measurement of buyers, squandering, embezzlement, robbing and theft of property, black market turnover. The circumstances of the incorporation of the phenomenon of fellowship and nepotism into the stable custom of everyday life are commented. The author comes to the conclusion that class conflicts emerged in the socio-economic structure of Soviet society in the 1960s — 1980s, while the urgent facts of the system’s crisis were generated by the duality of the line of power.